Lithostratigraphy and late Cenozoic fluvial styles of Siwalik Group along Kankai River section, East Nepal Himalaya (Bulletin of the Department of Geology, 2009)
This paper describes on lithostratigraphy as well as evolution of the fluvial styles in late Cenozoic Siwalik Group along the Kankai River section of east Nepal Himalaya. The Siwalik Group lies on the southern flank of the Himalaya, is composed of molasse sediments, which were derived from the rising Himalaya in the north. The group along the Kankai River section is lithologically divided into the Lower, Middle and Upper Siwaliks, in ascending order based on increasing grain size and lithology. The Lower Siwaliks is subdivided into the lower and upper members, whereas the Middle Siwaliks is subdivided into the lower, middle and upper members on the basis of the relative thickness of the sandstone and mudstone beds, frequency of occurrence of these beds, and grain size of sandstone. The Upper Siwaliks is subdivided into the lower and upper members based on the clast size in conglomerate and constituent of the Siwalik sandstone boulders in conglomerate. Based on the lithology, assemblages of sedimentary structure and sediment body architectures, seven facies associations (FA1 to FA7) are recognised. These facies associations are closely related to each lithostratigraphic units of the area. The sediments of the lower and upper members of the Lower Siwaliks are products of the fine-grained meandering and flood flow-dominated meandering systems, respectively. The lower, middle and upper members of the Middle Siwaliks are interpreted as the deposits by sandy meandering, deep sandy braided and shallow braided systems, respectively whereas the lower and upper members of the Upper Siwaliks are the products of gravelly braided to debris flow-dominated braided systems, respectively.   doi: 10.3126/bdg.v12i0.2251 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 63-74